2009
DOI: 10.1002/hyp.7287
|View full text |Cite
|
Sign up to set email alerts
|

Factors controlling the spatial variability of surface soil moisture within revegetated‐stabilized desert ecosystems of the Tengger Desert, Northern China

Abstract: Abstract:The spatial structure of surface soil moisture was investigated at a grid scale with 10 ð 10 m intervals on a plot of 4500 m 2 in a re-vegetated desert area in Shapotou, the Tengger Desert. The site topography varies from dune crest to dune hollow, and again to dune crest. Volumetric soil moisture contents were measured 21 times over 6 months in 2006 by using Delta-T Theta-Probes in the 0-6 cm surface soil layer before and after rainfall. At the same time, soil texture, relative elevation, and plant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
30
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 46 publications
9
30
1
Order By: Relevance
“…This study showed that shrub stemflow conserved in the deep soil layers can be an available moisture source for plant growth under arid conditions and that root channels were preferential pathways for the movement of most stemflow water into the soil. Similar experiments by Pan and Wang (2009) and Wang et al (2011b) gave consistent results. Small rainfall events usually affect only the uppermost cm of the soil and easily lost through direct evaporation, and the soil moisture was therefore mainly contributed by the large events (Schwinning and Sala, 2004).…”
Section: Introductionsupporting
confidence: 80%
“…This study showed that shrub stemflow conserved in the deep soil layers can be an available moisture source for plant growth under arid conditions and that root channels were preferential pathways for the movement of most stemflow water into the soil. Similar experiments by Pan and Wang (2009) and Wang et al (2011b) gave consistent results. Small rainfall events usually affect only the uppermost cm of the soil and easily lost through direct evaporation, and the soil moisture was therefore mainly contributed by the large events (Schwinning and Sala, 2004).…”
Section: Introductionsupporting
confidence: 80%
“…Land use can significantly affect soil properties, such as bulk density, saturated hydraulic conductivity, infiltration rate and available soil water content (Haghighi et al, 2010), and it has been shown to be one of the main factors controlling soil water variability (Qui et al, 2001;Pan and Wang, 2009). Because soil properties are the main factor controlling soil water variation (Vachaud et al, 1985, Famiglietti et al, 1998Hu et al, 2010), land use could influence soil water variations by changing soil properties (Gao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In Shapotou area of Tengger desert, more than 50 years of succession of artificial sand-binding vegetation and the regional restoration of eco-environment are the theoretical verification and successful example for the desertification reversion (Li 2005). Spatial heterogeneity of soil properties is evident in shrub-desert and steppe ecosystems due to the discontinuous distribution of vegetation (Gallardo et al 2000), and Shapotou area is an example of attempting this (Li 2005, Pan andWang 2009). Our results showed that there were gradual change gradients from C. korshinskii shrub stems towards the surrounding interspaces in soil moisture content, soil texture, bulk density, SOM, TN, EC and infiltration rate, indicating that the effect of shrub can extend to the outside of canopy.…”
Section: Discussionmentioning
confidence: 99%
“…Shrub vegetation enriches the soil under shrub canopies by a combination of biotic and abiotic processes (Schlesinger et al 1996), and changes the physical properties (Eldridge andRobson 1997, Whitford et al 1997), hydraulic characteristics (Neave and Abrahams 2002, CantÓn et al 2004, Pan et al 2008, Pan and Wang 2009, and biotic activity (Belsky et al 1989), which are the primary limiting factors for the structure, production and dynamics of vegetation in arid ecosystems (Aguiar andSala 1999, Kidron 2009). As such, a large number of herbaceous plants establish and grow, due to the "nurse plant" effect of shrubs (Li et al 2007).…”
Section: Introductionmentioning
confidence: 99%